Tumor lysis syndrome in childhood malignancies - Wing Lum Cheung; Kam Lun Hon; Cheuk Man Fung; Alexander KC Leung (BioExcel Publishing Ltd, 2020)
Background: Tumor lysis syndrome (TLS) is the most common life-threatening oncological emergency encountered by physicians treating children with lymphoproliferative malignancies. Healthcare providers should be aware of the condition in order to prevent occurrence and prompt timely management to avoid severe consequences. Objective: To provide an update on the current understanding, evaluation, and management of tumor lysis syndrome in childhood malignancies. Methods: A PubMed search was performed in Clinical Queries using the keywords 'tumor lysis syndrome' and 'malignancies' with Category limited to clinical trials and reviews for ages from birth to 18 years. Results: There were 22 clinical trials and 37 reviews under the search criteria. TLS is characterized by acute electrolyte and metabolic disturbances resulting from massive and abrupt release of cellular contents into the circulation due to breakdown of tumor cells. If left untreated, it can lead to multiorgan compromise and eventually death. Apart from close monitoring and medical therapies, early recognition of risk factors for development of TLS is also necessary for successful management. Conclusions: Prophylactic measures to patients at risk of TLS include aggressive fluid management and judicious use of diuretics and hypouricemic agents. Both allopurinol and urate oxidase are effective in reducing serum uric acid. Allopurinol should be used as prophylaxis in low-risk cases while urate oxidase should be used as treatment in intermediate to highrisk cases. There is no evidence on better drug of choice among different urate oxidases. The routine use of diuretics and urine alkalinization are not recommended. Correction of electrolytes and use of renal replacement therapy may also be required during treatment of TLS.